Implementing Lean Principles in DevOps for Efficiency and Cost Savings - Vidyasagar Vangala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Modern organizations embrace DevOps as a strategy aimed at optimizing operations, increasing teams’ interaction, and reducing delivery cycles in the ecosystem of software development. Most of the advantages that come with DevOps contribute to developmental delays and increased costs when implementation strategies are not well thought out. This paper examines the application of Lean principles within DevOps practices to implement improved operational efficiency and reduce waste, hence reducing costs. The original manufacturing application of Lean methodology underlined waste elimination, along with the simultaneous delivery of improved quality, and more value creation by optimization of operations. Value stream mapping, reduction of waste, and continuous improvement allow the DevOps teams to work on improving their delivery pipelines through automated collaboration and optimization of delivery pipelines. Reduction of operational prices, along with cycle times, ensues as a result. It tries to outline the specific implementation techniques of Lean in DevOps through enhanced workflow practices, establishment of continuous learning environments, and performance monitoring metrics development. The paper describes some case examples that talk about organizations that implemented Lean with DevOps methods for certain efficiency and quality performance improvements together with cost savings measurements. Organizations using Lean to DevOps processes have to implement changes in culture and ensure leadership commitment develop refining habits, leading to enduring success.